STRATEGI PENGEMBANGAN TANAMAN BAMBU DI KECAMATAN TENGGARONG SEBERANG KABUPATEN KUTAI KARTANEGARA - Aulia Wirahman; Erwin Prayogi; Taufan Tirkaamiana; Zikri Azham (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2022)
This study aims to determine to obtain socio-economic data on bamboo plants related to their use in the community in Tenggarong Seberang District, Kutai Kartanegara Regency, and to formulate a strategy for developing and managing bamboo plants based on local communities in Tenggarong Seberang District, Kutai Kartanegara Regency. This research uses cluster sampling method, while data analysis uses SWOT analysis. Cluster sampling method is carried out by collecting data from clusters that are used randomly according to needs taken from certain strata or groups, namely Farmers, Community, Traders, Community Leaders, and Dinas Lingkungan Hidup dan Kehutanan Kutai Kartanegara Regency. The results of the study show a socio-economic description of bamboo plants from the side of their use, namely several types of bamboo that have been found and identified in Tenggarong Seberang District including black bamboo, yellow bamboo, butar bamboo, china bamboo, petung bamboo and thorn bamboo. The main occupations of farmers in Tenggarong Seberang District are field farmers and sugar palm farmers. The selling price of bamboo at the farmer level is Rp. 500.00 for one stem. Meanwhile, the selling price of one ironwood stick for a plant pillar is Rp. 2,000.00. Then the strategy for developing and managing bamboo plants in Tenggarong Seberang District is appropriate for bamboo plant farmers, namely providing and setting boundaries between company forest areas and community forests and granting business permits and guarantees from the government.